Optimal orbit design for repeat-pass multi-baseline observation of tomographic SAR satellites. Issue 8 (15th April 2020) - Chen, Tianfu; Zhang, Dexin; Li, Wei; Shao, Xiaowei
Abstract: Tomographic synthetic aperture radar (TomoSAR) is a modern technique that allows retrieving the structural information of detected objects. This paper investigates the problem of optimal orbit design in TomoSAR space missions. Considering the mission requirement of multi-baseline repeated observation, the orbital characteristics of TomoSAR satellites are analysed under the J 2 perturbation effect. By introducing the performance indicators of sampling period and orbital transfer fuel consumption, the orbit design is transformed into a multi-objective optimization problem. A two-step optimization strategy is developed to find the optimal orbits of TomoSAR satellites. In the first step, where some approximations are made, the idea of Pareto optimal solutions is applied under the objectives of time and fuel. A more accurate model is utilized in the second refinement step, and biogeography-based optimization (BBO) is employed to obtain satisfactory revisit accuracy. Numerical simulations are conducted to testify the effectiveness of the suggested design process, providing references for TomoSAR missions in terms of satellite orbit.